2003
DOI: 10.1111/j.1365-2621.2003.tb12333.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Antifreeze Protein for Food Preservation: Effect of Type III Antifreeze Protein for Preservation of Gel‐forming of Frozen and Chilled Actomyosin

Abstract: Type III antifreeze protein (AFP) remarkably preserved Ca 2+ ATPase activity of actomyosin during frozen and chilled storage. Under frozen conditions, AFP helped to retain the Ca 2+ ATPase activity of actomyosin much higher than that of conventional cryoprotectants (sucrose-sorbitol mixture). The Ca 2+ ATPase activity increased with increasing AFP concentration and reached a maximum at 50g/L AFP. After 3-d chilled storage, the Ca 2+ ATPase activity of control and sucrose-sorbitol samples had lost 80% and 50%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…AFPs remarkably preserved Ca 2+ ATPase activity of actiomyosin during storage and provided better protection than conventional cryoprotectants such as sucrose-sorbitol mixtures. 134 A Unilever patent suggested that fungal hydrophobin AFPs inhibited ice crystal growth during frozen storage (i.e., ice recrystallization) and modified ice crystal shape in aerated and non-aerated frozen food products. 135 Although commercial AFPs are currently available, they are mainly for research or special uses because of their high price.…”
Section: Applications Of Afps In Food Technology and Perspectivesmentioning
confidence: 99%
“…AFPs remarkably preserved Ca 2+ ATPase activity of actiomyosin during storage and provided better protection than conventional cryoprotectants such as sucrose-sorbitol mixtures. 134 A Unilever patent suggested that fungal hydrophobin AFPs inhibited ice crystal growth during frozen storage (i.e., ice recrystallization) and modified ice crystal shape in aerated and non-aerated frozen food products. 135 Although commercial AFPs are currently available, they are mainly for research or special uses because of their high price.…”
Section: Applications Of Afps In Food Technology and Perspectivesmentioning
confidence: 99%
“…This pathogenic number reduction was as a result of a presence of low temperature (<10 C) and chlorine of the cold solution. Chlorine has been reported as an excellent sanitizer; normally reducing microbial number by up to 1 Log-cycle (Chaiyakosa, Charernjiratragul, Umsakul, & Vuddhakul, 2007;Husna & Lin, 2001). Sizing of prawn (from points C to D) …”
Section: Behavior In a Factorymentioning
confidence: 98%
“…The properties of AFPs include depressing freezing temperature without affecting the melting temperature (so‐called TH) (Boonsupthip and Lee ; Kontogiorgos et al . ; Zhang et al .…”
Section: Function and Mechanism Of Actionmentioning
confidence: 99%